1989
DOI: 10.1079/pns19890048
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition, Immune Function, and Inflammation: an overview

Abstract: The account of acute inflammation is one of the classical clinical descriptions in medicine. However, those early physicians describing Rubor et tumor cum calor et dolore (Celsus in 50 BC) could hardly have imagined the complexity of the events that they were observing.In a healthy individual, the response to tissue injury and infection is rapid and efficient, with resolution occurring before involvement of the specific immune system. However, when the inflammatory stimulus is overwhelming, or if the patient i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(17 citation statements)
references
References 139 publications
0
17
0
Order By: Relevance
“…Moreover, body mass might simply reflect nutritional condition, which can influence survival via its effect on immunocompetence (Willis & Baker 1981;Tsiagbe et al 1987;Lochmiller, Vestey & Boren 1993). Studies in this field have shown that parasite morbidity is influenced by host dietary protein and amino acid levels, indicating that quality of food can influence the impact of parasites through an effect on host immune function (Willis & Baker 1981; see also Wan, Haw & Blackburn 1989). In this particular scenario, body mass would simply be a correlate of survival rather than one of its determinants.…”
Section: ; Bryantmentioning
confidence: 95%
“…Moreover, body mass might simply reflect nutritional condition, which can influence survival via its effect on immunocompetence (Willis & Baker 1981;Tsiagbe et al 1987;Lochmiller, Vestey & Boren 1993). Studies in this field have shown that parasite morbidity is influenced by host dietary protein and amino acid levels, indicating that quality of food can influence the impact of parasites through an effect on host immune function (Willis & Baker 1981; see also Wan, Haw & Blackburn 1989). In this particular scenario, body mass would simply be a correlate of survival rather than one of its determinants.…”
Section: ; Bryantmentioning
confidence: 95%
“…In a recent study, we found several nutritional and functional de®ciencies in patients with longstanding CD, currently in remission (Geerling et al, 1998a, b). It is known that malnutrition is associated with immune dysfunction (Gallagher & Daly, 1993;Grimble, 1994;Wan et al, 1989) and increased susceptibility to oxidative tissue damage (Halliwell, 1994). Adequate nutritional support may be an important therapeutic tool in improving the nutritional status and attenuating the in¯ammatory process in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Another beneficial effect of fumaric acid supplementation may be the reduction of the LPS content in digesta. LPS is a potent endotoxin (Mayeux 1997), which can be absorbed in the systemic circulation via the gastrointestinal tract (Wan et al 1989), but the mechanism of absorption remains still unclear. Benoit et al (1998) demonstrated in in vitro studies with rats that isolated lipopolysaccharides do not pass across the intestinal mucosa, not even after disruption of the intestinal epithelium with a potent mucolytic agent.…”
Section: Discussionmentioning
confidence: 99%